2022
DOI: 10.2174/1389557521666211124141859
|View full text |Cite
|
Sign up to set email alerts
|

Chromone, A Privileged Scaffold in Drug Discovery: Developments in the Synthesis and Bioactivity

Abstract: : Chromones are the class of secondary metabolites broadly occurred in the plant kingdom in a noticeable quantity. This rigid bicyclic system has been categorized “as privileged scaffolds in compounds” in medicinal chemistry. The wide biological responses made them an important moiety in a drug discovery program. This review provides updates on the various methods of synthesis of chromones and biological applications in medicinal chemistry. Various synthetic strategies for the construction of chromones include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 181 publications
0
14
0
Order By: Relevance
“…Chromones are benzoannelated γ-pyrone (4 H -chromen-4-one, 4 H -1-benzopyran-4-one) based heterocyclic motifs present in many natural products, pharmaceuticals as well as in the molecules with enriched biological functions. Chromone and its derivatives have shown numerous biological activities such as anticancer, anti-inflammatory, antidiabetic, antimalarial, and neuroprotective activity. They also showed a potential as tyrosine phosphatases inhibitors, HIV inhibitors, topoisomerases inhibitors, phosphodiesterase inhibitors, leukotriene receptor antagonists, and so on. , Therefore, the synthesis of functionalized chromones has received considerable attention owing to their above-mentioned unique biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Chromones are benzoannelated γ-pyrone (4 H -chromen-4-one, 4 H -1-benzopyran-4-one) based heterocyclic motifs present in many natural products, pharmaceuticals as well as in the molecules with enriched biological functions. Chromone and its derivatives have shown numerous biological activities such as anticancer, anti-inflammatory, antidiabetic, antimalarial, and neuroprotective activity. They also showed a potential as tyrosine phosphatases inhibitors, HIV inhibitors, topoisomerases inhibitors, phosphodiesterase inhibitors, leukotriene receptor antagonists, and so on. , Therefore, the synthesis of functionalized chromones has received considerable attention owing to their above-mentioned unique biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various different functionalizations of chromone core, keeping a carboxylic acid group at 2-position ( 1 , Figure ) has been increasingly gaining the attention of medicinal chemists as the preferred functional group modification, , because chromone-2-carboxylic acids ( 1 ) and their other derivatives (like amides and tetrazoles) have been found to exhibit diverse biological properties with improved physical properties. ,, For example, traditionally, the naturally occurring chromone derivative khellin ( 2 ) has been used as a bronchodilator in the pure form (as a drug) and for other treatments as a plant extract in herbal medicine . But it was found that the pure form of khellin has inherent severe side effects and a poor water-solubility profile.…”
mentioning
confidence: 99%
“…Chromone moiety , is the fundamental nucleus present in several phytochemicals (like flavones, isoflavones, and other chromone derivatives) abundant in the diet rich in vegetables, fruits, cereals, etc. , Since ancient times, their applications in herbal medicines for different pharmacological purposes have been well documented. And numerous chromone-based synthetic compounds have been reported to exhibit diverse biological properties, such as antiallergic, antioxidant, antitumor activity, antihepatotoxic activity, antispasmolytic, anti-inflammatory, antifungal, antimicrobial, antibacterial activities, and HIV-inhibition properties. Thus, the chromone nucleus has been recognized as one of the privileged heterocyclic scaffolds in the medicinal chemistry. …”
mentioning
confidence: 99%
See 2 more Smart Citations